DESIGN OF AUTOMATIC HAND WASHING SYSTEM USING SOLENOID VALVE BASED ON MICROCONTROLLER - Muhammad Furqon Siregar; Chairul Imam (Sean Institute, 2022)
Nowadays, technology is evolving with the times. Technology is applied and makes it easier for humans to carry out all activities. Researchers take the initiative to see and use technology in daily life, supporting our health. From the research of the results in the field, researchers find problems with washing hands. Everyone is still interacting directly by holding the faucet and soap bottle. From this habit, the virus can be reattached to the hands through the faucet that people have held before. From the research analysis, researchers will make designs to prevent the spread of viruses and bacteria by washing hands. This is an intelligent system design, where is the system integrated with a microcontroller. The prototype system uses a fully automated sensor implementation. It is hoped that this prototype can be applied by segments of the wider community. Keywords: Technology for Health, Prototype, Innovation Smart System Design